Sufisme Urban: Oase Ketenangan Batin Di Tengah Hiruk Pikuk Modernitas - Putra, Zulfikar; Thalib, Syamsul Bachri; Arifin, Muhamad; Murdiansyah, Eko Bambang; Prasetyo, Bagus Eko (Spiritualita, 2025)
The fast-paced, stressful, and individualistic nature of urban life often triggers spiritual crises and a sense of meaninglessness among urban communities.  The purpose of this study is to analyze the significant role of Sufism in addressing the challenges of the complexity of urban life. The method used is qualitative research with a literature review approach, with data sources drawn from scientific journals, books, papers, and other secondary sources. The results of this study indicate that Sufism is not only relevant but also plays a significant transformative role in urban life. This can be seen from several indicators, including the acknowledgment by some individuals that Sufism serves as an effective remedy for spiritual emptiness and psychological stress amid the complexities of urban life. The conclusion is that Sufism emerges as a spiritual solution that not only offers inner peace and spiritual tranquility but also helps individuals rediscover the lost meaning of life and achieve a harmonious balance between worldly demands and spiritual needs.